2000
DOI: 10.1038/sj.bjp.0703499
|View full text |Cite
|
Sign up to set email alerts
|

Selective modifiers of glutathione biosynthesis and ‘repriming’ of vascular smooth muscle photorelaxation

Abstract: 1 Photorelaxation of vascular smooth muscle (VSM) is caused by the release of nitric oxide (NO) from a ®nite molecular store that can be depleted by irradiating pre-contracted arteries with visible light. The ability of an`exhausted' vessel to respond to a further period of illumination is lost temporarily but then recovers slowly as the photosensitive store is reconstituted in the dark. The recovery process, termed repriming, displays an absolute requirement for endothelium-derived NO and is inhibited by pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…It has been proposed that low molecular weight thiols such as glutathione and cysteine, which react with nitric oxide or oxides of nitrogen to form nitrosothiols, are potential candidates for a nitric oxide-carrier molecule [16,17]. Endogenous nitrosothiols, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that low molecular weight thiols such as glutathione and cysteine, which react with nitric oxide or oxides of nitrogen to form nitrosothiols, are potential candidates for a nitric oxide-carrier molecule [16,17]. Endogenous nitrosothiols, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…S-nitrosoglutathione, generated from the interaction of GSH with peroxynitrite, releases NO in a time-dependent manner from vascular tissues (Balazy et al, 1998) or in a light-sensitive manner from cultured leukemia cells (Sexton et al, 1994). In fact, even GSH alone can be a light-sensitive intracellular NO pool (Megson et al, 2000).…”
Section: Interaction Of Heme Oxygenase/carbon Monoxide and Nitricmentioning
confidence: 99%
“…Indeed, nitrite ions do undergo NO photolysis, showing a maximum around 354 nm (15). Other studies claimed to have identified RSNOs (16)(17)(18) as the chemical species responsible for photorelaxation. However, they possess a UVabsorption band peaking in the 330-to 340-nm range (19,20), which does not coincide with any of the action spectrum peaks reported in previous studies.…”
mentioning
confidence: 99%